PENGARUH KINERJA KEPALA DESA TERHADAP PENGEMBANGAN EKONOMI MELALUI BUMDES DI DESA MARIO KABUPATEN BONE - Syarifah Rafikah; Sri Ayu (Universitas Ichsan Sidenreng Rappang, 2026)
This study aims to determine the effect of village economic development through village-owned enterprises on the performance of the village head of Mario Village, Libureng Subdistrict, Bone Regency. This study employs a quantitative research method and was conducted in Bone Regency, specifically in Mario Village, Libureng Subdistrict, Bone Regency, as well as other locations relevant to the research subject. The data used were primary data obtained from interviews and questionnaires administered to 112 respondents. The results of the analysis, using Path Analysis and Correlation Coefficient Analysis, showed a significant effect on village head performance. Data analysis was performed using the Classical Assumptions Test with SPSS software. The results of this study indicate that the variables in this study consist of Village Head Performance (X), Village-Owned Enterprises (BUMDes) (Z), and Village Economic Development (Y).